NAWAL AL-SA’ADAWI DALAM PEREMPUAN DAN SEKS; PERSOALAN KHITAN BAGI PEREMPUAN DITINJAU DARI KESEHATAN DAN ISLAM - Fuad Mahbub Siraj (Universitas Paramadina, 2014)
AbstractNawal al-Sa'adawi is a doctor from Egypt who is also famous as a writer, novelist and feminist. He raised the issue of gender in his work Almar'ah wa al-Jins (Women and Sex) that associated with the issue of circumcision for women. Generally in the world and particularly in the Egypt, the emergence of circumcision became a tradition among the people, the problem that is always